Optimal control of mode transition from hybrid to electric mode under turning deceleration conditions for four-wheel-drive HEV with DCT. Issue 2 (1st February 2022) - Zhao, Zhiguo; Fu, Shihao; Jiang, Siwen; Lei, Dan
Abstract : When a four-wheel-drive hybrid electric vehicle (HEV) with dual clutch transmission (DCT) is decelerating while turning, the vehicle often transits from front-wheel hybrid mode to electric mode of the rear hub motors, in order to improve the energy efficiency. However, the mode transition process is accompanied by the driving torque front-to-rear axis conversion and the wheel load transfer. And the mode transition process involves not only the torque coordinated control of the multi-power sources, but also the differential control of the left and right rear hub motors. If not properly controlled, it will cause a large jerk and  the vehicle to be unstable. In this paper, a seven degrees of freedom (DOF) of vehicle model integrated with DCT powertrain system is introduced to reflect its lateral and longitudinal dynamic characteristics in the mode transition process. The optimal control strategy considering the differential distribution of the rear hub motors' torque is proposed based on sliding-mode control (SMC). Simulation and hardware-in-the-loop (HIL) test results show that the proposed mode transition control strategy can not only achieve smooth front- to rear-end driving torque switching and reduce the jerk 5.7%, but also improve the tracking performance of side slip angle and the yaw rate.